1985
DOI: 10.1103/physreva.31.2610
|View full text |Cite
|
Sign up to set email alerts
|

Probability of electrical breakdown: Evidence for a transition between the Townsend and streamer breakdown mechanisms

Abstract: Spark-breakdown delay times were measured for N2, H2, Ar, SF6, and CC12F2 in a uniform field gap provided with a small current (-10 ' A) of free electrons by uv illumination of the cathode. Laue plots of the delay times yielded straight lines with slope iP, where i is the photocurrent and P is the breakdown probability. The dependence of the breakdown probability on voltage for N2, H&, and Ar was in good agreement with predictions of the Townsend breakdown mechanism. In SF6 and CC12F2, a transition was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…On the other hand, we note that streamer velocities, in both natural and industrial contexts, are typically orders of magnitude higher than our observed speed. 27 Thus, in this respect plasma globe filaments appear to represent a sort of slow streamer. This discharge regime may also possibly be influenced by thermal ionization instability.…”
Section: E Filament Origins and Propagationmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, we note that streamer velocities, in both natural and industrial contexts, are typically orders of magnitude higher than our observed speed. 27 Thus, in this respect plasma globe filaments appear to represent a sort of slow streamer. This discharge regime may also possibly be influenced by thermal ionization instability.…”
Section: E Filament Origins and Propagationmentioning
confidence: 98%
“…26 Thus, near atmospheric pressure, a is of order unity, and for our 8 cm gap we are probably in excess of the Meek criterion. Based on these empirical rules, we expect some degree of streamer activity within the globe (though which breakdown mechanism dominates the discharge each cycle is considered to be, ultimately, probabilistic 27 ).…”
Section: E Filament Origins and Propagationmentioning
confidence: 99%
“…The distribution of the dynamic breakdown voltages U b for an inhomogeneous Poisson process is given by [15]:…”
Section: Fitting the Experimental Distributionsmentioning
confidence: 99%
“…These rate coefficients in (14) and (15) are defined in relation to the gas-phase number density of nitrogen atoms [2,22]. The initial number density of nitrogen atoms is assumed to be [N 0 ] = 3 × 10 9 cm −3 which corresponds to about 1 ppm impurity contents of nitrogen in argon and typical degree of dissociation of ∼ 10% [34,35] (Fig.…”
Section: Relaxation Kinetics In Argon Afterglowmentioning
confidence: 99%
“…The transition regime between Townsend and streamer mechanism is described in [6]. The electrical breakdown in gases is of a stochastic nature as the result of the statistical behavior of the processes, which lead to it.…”
Section: Introductionmentioning
confidence: 99%